2013
DOI: 10.1080/00223131.2013.785266
|View full text |Cite
|
Sign up to set email alerts
|

Intergranular stress corrosion cracking initiation model of austenite stainless steels used in BWRs for optimized water chemistry control

Abstract: A calculation model on intergranular stress corrosion cracking (IGSCC) initiation time of materials used in boiling water reactors (BWRs) has been developed to evaluate effectiveness of water chemistry control for mitigation of the IGSCC. The model was composed of four terms which determine passive film break time:(1) a chemical term based on electrochemical corrosion potential (ECP) and impurity concentration; (2) a mechanical term based on strain rate; (3) a material term based on sensitization; and (4) an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…It was reported that gamma-ray irradiation promoted corrosion of SS [22,23]. Then, the anodic current of the 316L SS oxidation may increase enough to lower the ECP of 316L SS while overcoming the increase of DO and DHP by radiolysis of seawatermixed water.…”
Section: Ecp Measurementsmentioning
confidence: 99%
“…It was reported that gamma-ray irradiation promoted corrosion of SS [22,23]. Then, the anodic current of the 316L SS oxidation may increase enough to lower the ECP of 316L SS while overcoming the increase of DO and DHP by radiolysis of seawatermixed water.…”
Section: Ecp Measurementsmentioning
confidence: 99%